345 INITIAL CHARACTERIZATION OF EFFECTS OF THE N-METHYL-D-ASPARTATE AGONIST 1-AMINOCYCLOBUTANE-CIS-1, 3-DICARBOXYLIC ACID ON GLUTAMATE-EVOKED EXCITATORY JUNCTIONAL POTENTIALS AT A CRAYFISH NEUROMUSCULAR JUNCTION. Issue 1 (1st January 2007) - Hall, G.; Bohnstedt, B. N.; Lastfogel, J.; Kinon, M. D.; Hasan, R.; Friedman, R. N.
Abstract : Background: Secondary injury following spinal cord trauma can include sequelae of glutamate excitotoxicity (GE). A crayfish walking limb neuromuscular junction (NMJ), having NMDA glutamate receptors, may be a useful model for studying potential GE mechanisms and countermeasures. This project examines the effects of 1-aminocyclobutane-cis-1, 3-dicarboxylic acid (ACDA), a potent glutamate agonist in vertebrate nervous systems, on excitatory junctional potentials (EJPs) at crayfish ( Procambarus clarkii and simulans ) NMJs. Methods: Crayfish first and second walking limbs were dissected to expose the dactylopodite opener muscle and the single, excitatory axon innervating it. Standard intracellular electrophysiologic techniques were used to measure EJPs. The opener muscle, located in the proprodite, and its excitatory axon, in the meropodite, were exposed and bathed in van Harreveld's solution (VanH) pH 7.2 ± 0.1. Van H was removed, and ACDA in vanH at 100 μM was added to exposed opener muscles. EJPs were measured at 1- and 2-minute intervals for each data collection. Short-term facilitated EJPs were evoked by 10-second stimulation at 30 Hz, then EJPs were averaged for 10 seconds. Results: EJPs in 100 μM ACDA-treated preparations showed partial suppression, ranging from 17 to 44% of control amplitude, with return to nearly control level (approximately 90%) following vanH wash with at least three complete exchanges of the bath. Qualitatively similar results were obtained using six separate limb preparations. Discussion: Suppression of EJPs by the NMDA agonist ACDA was unexpected as the crayfish NMJ has NMDA receptors and glutamate is the excitatory neurotransmitter. A complete concentration:response study is warranted to determine if ACDA acts as an agonist at lesser concentrations. It is also possible that the invertebrate and vertebrate receptors have different responses to ACDA. However, at the 100 μM concentration, ACDA should not be ruled out for studies of means of reducing glutamate excitotoxicity. Arnold C., Barbara M. and Georgianna Fossa Spinal Cord Injury Research Fund and the Indiana University Brain and Spinal Cord Injury Research Program.